UM-SCC-104: a new human papillomavirus-16 containing head and neck squamous cell carcinoma cell line - Tang, Alice L. (2011)
BACKGROUND: Few human papillomavirus (HPV)-positive head and neck squamous cell carcinoma (HNSCC) cell lines exist. We established UM-SCC-104, a new HPV(+) HNSCC cell linefrom a recurrent oral cavity tumor, and characterized it for the presence of cancer stem cells (CSC). METHODS: Tumor cells were tested for biomarker expression by immunohistology and the presence of HPV was assessed by several methods. RESULTS: UM-SCC-104 has a unique genotype, contains HPV-16 and expresses E6/E7. Inoculation of (Aldehyde Dehydrogenase) ALDH(+) and ALDH(−) cells in an immunocompromised mouse resulted in tumor growth from the ALDH(+) cells after 6 weeks that recapitulated the histology of the primary, while ALDH(−) cells did not produce tumors. CONCLUSIONS: UM-SCC-104, a new HPV-16, CSC-containing HNSCC cell line will aid in studying recurrent HPV(+) tumors. The aggressive nature of this tumor is consistent with high uniform expression of EGFR and a functionally significant proportion of ALDH(+) CSC.